THE STATUS OF FULL AND ON- SCHEDULE VACCINATION WITH 8 TYPES OF VACCINES AMONG CHILDREN UNDER 1 YEAR OLD AT QUAN TRIEU WARD, THAI NGUYEN CITY (Vietnam Journal of Community Medicine, 2021)
Vaccination is one of the greatest achievements of modern medicine. The expanded program onimmunization has significantly reduced the morbidity and the mortality of children under 5 years oldcaused by infectious diseases. Alongside the achievements of the expanded program on immunization,in recent years, some diseases that had vaccines still outbroke in some locals. To improve theefficiency of the vaccination program, we conduct this study with this following target: To describethe status of full and on schedule vaccination with 8 types of vaccines among children under 1 yearold at Quan Trieu Ward, Thai Nguyen City. Research subjects and methods: The descriptive, crosssectional study was conducted among 105 children by immediately interviewing the major caregiversand checking the vaccination records. Research results: The complete vaccination coverage for eachvaccine: Hepatitis B: 99%, TB: 100%, DPT-Hib: 99%, polio: 99% and measles: 100%. The rates ofon-schedule vaccination for each type of vaccines are: Hepatitis B: 83.8%, TB: 87.6%, DPT-Hib:83.8%, polio: 83.8% and measles: 71.4%. The complete vaccination coverage of 8 types of vaccinesis 99% whilst the on-schedule vaccination rate of 8 types of vaccines is only 57.1%.
Keywords: The expanded program on immunization, full vaccination, on schedule vaccination, vaccines, children under 1 year old